2019
DOI: 10.1021/acs.nanolett.9b03783
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline γ-Ga2S3 Nanotubes via Epitaxial Conversion of GaAs Nanowires

Abstract: The chemical transformation of nanowire templates into nanotubes is a promising avenue toward hollow one-dimensional (1D) nanostructures. To date, high-quality single crystalline tubes of non-layered inorganic crystals have been obtained by solid-state reactions in diffusion couples of nanowires with deposited thin film shells, but this approach presents issues in achieving singlephase tubes with a desired stoichiometry. Chemical transformations with reactants supplied from the gas-or vapor-phase can avoid the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The tubes formed by retraction of GaAs cores due to injection and coalescence of vacancies into the Kirkendall voids, with simultaneous evaporation of As. 32 In this paper, we demonstrate that freestanding Ga 2 Se 3 NWs can be obtained by MBE on Au-decorated GaAs surfaces without any external Ga supply, via a heterovalent exchange reaction mediated by Au nanoparticles. We show that at a suitable temperature the presence of Au on the surface favors the decomposition of the GaAs substrate and the release of Ga atoms, which react with the incoming Se and feed the NW growth.…”
Section: ■ Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The tubes formed by retraction of GaAs cores due to injection and coalescence of vacancies into the Kirkendall voids, with simultaneous evaporation of As. 32 In this paper, we demonstrate that freestanding Ga 2 Se 3 NWs can be obtained by MBE on Au-decorated GaAs surfaces without any external Ga supply, via a heterovalent exchange reaction mediated by Au nanoparticles. We show that at a suitable temperature the presence of Au on the surface favors the decomposition of the GaAs substrate and the release of Ga atoms, which react with the incoming Se and feed the NW growth.…”
Section: ■ Introductionmentioning
confidence: 78%
“…The nanostructures showed excellent nonlinear optical properties. Finally, single crystalline Ga 2 S 3 nanotubes were obtained by conversion of GaAs NWs exposed to sulfur vapor . The conversion process was investigated as a function of the exposure time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the controllable preparation of Ga 2 S 3 nanostructures remains a challenge. Up to now, the synthesis mainly focuses on the template-assited method followed by a thermal treatment [64,129,[131][132][133]. Hiring metal-organic frameworks (MOFs, MIL-96) as template precursor accompanied by a sulfuration process, Wang et al obtained dodecahedral Ga 2 S 3 /C structures, as is shown in Fig.…”
Section: Gallium Sulfide Anodesmentioning
confidence: 99%